Multimodal MRI reveals distinct hippocampal subregional alterations in de novo Parkinson’s disease across the cognitive spectrum - Pan, Chenxi; Zhao, Enchun; Ren, Jingru; Zhou, Gaiyan; Wang, Yajie; Zhang, Ronggui; Shen, Yang; Liu, Weiguo; Chen, Jiu (Frontiers in Aging Neuroscience, 2025)
BackgroundHippocampal subregion atrophy has been associated with cognitive decline in Parkinson’s disease (PD). Our study aimed to investigate the functional and structural alterations of the hippocampal subregion in newly diagnosed PD patients presenting with different cognitive states and to explore potential associations between these neuroanatomical alterations and cognitive performance.MethodsA total of four participant groups were recruited, including a de novo PD patient with mild cognitive impairment (PD-MCI, n = 44), a de novo PD patient with subjective cognitive decline (PD-SCD, n = 11), a de novo PD patient with normal cognition (PD-NC, n = 28), and a healthy control (HC, n = 19). The functional connectivity (FC) and gray matter (GM) volume alterations in the anterior, middle, and posterior regions of the left hippocampus were investigated. Moreover, we explored their relationship with cognition.ResultsCompared to the PD-NC, the PD-SCD group revealed a significantly decreased FC between the left middle hippocampus (HIPm) and right postcentral gyrus (PoCG. R). Patients in the PD-MCI group had a decreased FC value not only between HIPm and PoCG. R but also between the left anterior hippocampus (HIPa) and PoCG. R. The GM volume in HIPa of PD-NC patients was significantly higher than that of PD-MCI patients. Furthermore, partial correlation analysis indicated that the FC in HIPa-PoCG. R and HIPm-PoCG. R was positively associated with executive functions. The elevated GM volume in HIPa was associated with better visuospatial and language functions.ConclusionDysfunction of left HIPm may contribute to initial executive decline in PD. The different subregions of the long-axis hippocampus could be targeted for early intervention strategies in PD with different cognitive states in the future.